Numerical simulation on transient thermal and hydraulic characteristics in sodium pool of CEFR under OPT-SLOOP and OPT-RHROSL conditions. (15th September 2021) - Liang, Jiangtao; Lu, Daogang; Fu, Jingpin; Zhao, Haiqi; Liu, Yizhe; Yang, Jun; Ma, Xiangfeng; Tang, Jiaxuan; Zhang, Yuhao
Highlights: A detailed 3-D CFD model of the CEFR primary circuit system is established. Two loops asymmetric coast-down and failure pump backflow are simulated. Asymmetric thermal and flow features are compared under OPT-SLOOP and OPT-RHROSL. Abstract: One Pump Trip (OPT) may cause asymmetric phenomena in China Experimental Fast Reactor (CEFR) primary system. Not only two loops asymmetric coast-down processes and failure pump backflow, but superposition loss of off-site power (SLOOP) or residual heat removal of single loop (RHROSL) with OPT may make the situation more complicated. In order to investigate transient thermal hydraulic characteristics in sodium pool under OPT-SLOOP and OPT-RHROSL conditions, a full-scale numerical 3D model of sodium pool in CEFR was established, in which the transient processes of coast-down and backflow were simulated. The simulation results revealed that, in the case of OPT-SLOOP, the intact loop overall temperature was significantly higher than the failure loop overall temperature in the cold sodium pool, and the maximum IHX outlet temperature difference between the two loops reached 125.7 ℃, while in the case of OPT-RHROSL, the maximum IHX outlet temperature difference was limited to 15 ℃.